DIALOG AL-QURAN DENGAN BUDAYA LOKAL NUSANTARA: RESEPSI AL-QURAN DALAM BUDAYA SEKATEN DI KERATON YOGYAKARTA - Muhammad Nurdin Zuhdi; Sawaun Sawaun (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2017)
This article examines the culture of Sekaten in the palace of Yogyakarta. Sekaten derived from the word Syahadatain is a religious social phenomenon created by Sunan Kalijaga as a means of spreading Islam in the land of Java. The focus of the study of this article is to examine the reception of the Qur'an in the Sekaten culture. this article is the result of research using cultural acculturation approach. From the analysis that has been done, it can be concluded that Sekaten is a religious social phenomenon that was created as a da'wah strategy in grounding the values of the Qur'an. in order to ground the values of the Qur'an, Sekaten combines three important elements, namely religion, culture, and economy. The integration of these three elements is represented by three important symbols of civilization for the people of Yogyakarta and its surroundings, namely the triangle formed between the Yogyakarta Palace as the cultural center, the Great Mosque as the center of Religion, and Pringharjo Market as the economic center.